Мобільна телефонія в матриці міського життя - Петренко-Лисак, Алла Олександрівна; Петренко-Лысак, Алла Александровна; Petrenko-Lysak, Alla O. (My University, 2016)
У статті вміщено міркування з приводу трансформацій у місті й міському житті поряд із появою в комунікативних практиках містян мобільного телефона або смартфона. Проаналізовано процеси і явища, що презентують взаємний вплив еволюції простору міста та інформаційно-комунікативних технологій. Зауважено на тому, що, попри помітні зміни, вітчизняна наука не представила світовій академічній спільноті потужного й суттєвого аналізу цих процесів в Україні. В статье речь идет о трансформациях, которые происходили и происходят в городской жизни и привели к изменениям в укладе городской жизни. Обращается внимание на информационно-коммуникативные технологии, а именно мобильную телефонию, которая, благодаря мобильному Интернету и смартфонам, привела к изменениям во взаимоотношениях горожан не только друг с другом, но и в отношениях между городским пространством, администрацией, городскими сообществами и отдельными индивидами. When cities has appeared telephone urban space has changed. Especially, changes became visible when the phone has become a mobile. Mobile telephony brought with it changes in interpersonal and institutional communication. Modern mobile phone is smartphones, tablets and mobile apps. Urban space progressively «is registered» inside the firmware of smartphones. Mobile applications, mobile etiquette, mobile Urbanism is the modern city life components make up the matrix of urban communicative, communication with city. The basis of newest inequalities formed. The limits of modern cities are determined by capacity communications systems (transportation, telephone and other communication systems, their reach and speed). Mobile phones and the Internet, not only in the big city, but a small village – is not a whim and not a luxury but a necessity. In the past, infrastructure projects entirely dependent on the officials and management in cities. Now and in the near future the number of platforms which will provide an opportunity for citizens to coordinate and organize themselves without the mediation of the city authorities increase. Sociology Science and Urban Studies in Ukraine only commence active and thorough search on the issue and clarify the state to study the interaction of urban spaces and townspeople and visitors through the mediation of information and communication technologies. But unfortunately, in Ukraine, experts who study this aspect comprehensively enough to present a detailed scientific national product for the world scientific community.
Mobile Telephony in the Urban Life Matrix
Keywords: місто; простір; мобільний телефон; смартфон; город; пространство; мобильный телефон; смартфон; city; space; mobile phone; smartphone